The Influence of School Principal Leadership and Teacher Commitment on Teacher Performance - Arina, Yudela; Sabandi, Ahmad; Rusdinal,; Rifma, (Indonesian Research Journal in Education |IRJE|, 2024)
The research aimed to describe (1) the correlation between principal leadership and teacher commitment, (2) the partial influence of principal leadership on teacher performance, (3) the partial influence of teacher commitment on teacher performance, and (4) the influence of principal leadership and commitment on teachers simultaneously on teacher performance. It used a quantitative approach with the relationship pattern between variables depicted in the path diagram. The population was 482 teachers from 53 schools, while the sample was 144 teachers selected from each school based on a proportional formula. The Likert scale questionnaire was validated and reliable and facilitated data collection. By using path analysis techniques, research data was processed. The results of the research revealed that a summary of the hypotheses was (1) there is a correlation between principal leadership and teacher commitment, (2) there is a direct influence of principal leadership and teachers on teacher performance, and (3) there is an indirect influence of principal leadership and teacher commitment on teacher performance. 1.